Seasonal Incidence and Extent of Damage Caused by Citrus Leaf Miner, Phyllocnistis citrella Stainton Infesting Lemon (Biological Sciences - PJSIR, 2005)
The seasonal incidence and extent of damage caused by citrus leaf miner, Phyllocnistis citrella Stainton (Lepi- doptera : Gracillariidae) were investigated during a styudy carried out in a citrus orchard at Faridpur, Bangladesh. The leaf miner was active throughout the year, and its incidence and extent of damage varied significantly in different months. It was observed that the trend of rising and falling of the pest level occurred twice in a year, with two peak populations in the months of April and September. The minimum incidence was found in January and July. The extent of damage in respect of percentage of leaf infestation, area of leaf infestation and the mine length per leaf were, respectively, 80%, 60%  and12.8 cm in April, and 64.9%, 50.06% and 10.4 cm in September. The environmental temperature and relative humidity of spring and autumn influenced the incidence of citrus leaf miner resulting in higher pest population and plant damage. The low environmental temperature in the winter months and excessive rainfall in the monsoon season adversely affected the pest in the field. The moderate environmental conditions of spring and autumn were, therefore, the most favourable periods for P. citrella in Bangladesh.